Interdisciplinary Journal of Papua New Guinea University of Technology : a platform for scholarly works from all disciplines of study (Unitech Printery, 2024)
Research plays pivotal role in advancing knowledge contribution for broader societal advancement. This journal is a platform that promotes discipline wide knowledge sharing and collaboration, drawing contributors and experts from different faculties of the PNG University of Technology to research and publish peer-reviewed articles. The articles in this journal reflect depth and breath of research conducted at the PNG University of Technology and cover wide variety of topics and perspectives in the fields of engineering, natural sciences, social sciences, business and other areas.